Slovenska podjetja in krožno gospodarstvo: Slovenski podjetniški observatorij 2017 - Denac, Matjaž; Močnik, Dijana (University of Maribor Press, 2018)
Slovenian Companies and Circular Economy : Slovenian Entrepreneurship Observatory 2017. In this paper, we first analysed all companies and entrepreneurs in Slovenia for the year 2016, then we compared for the year 2015 or 2014 key data of Slovenia and EU-28 or individual member states in the non-financial business economy (the activities of industry, distributive trades and services). In Slovenia, in 2016 124,058 businesses employed 543,371 people. The majority of businesses (nearly one fifth) operated in the wholesale and retail trade; maintenance and repair of motor vehicles. Likewise, in the EU-28 in 2015 more than a quarter of businesses (26.4% or 6.2 million) was active in the wholesale and retail trade; maintenance and repair of motor vehicles. This activity employed the most people, almost a quarter (33.1 million). In the EU-28 as well as in Slovenia, the majority of value added was created by manufacturing businesses. The average value added per person employed for the aggregated activities of the EU-28 in the year 2015 amounted to 51,086 euros, while in Slovenia 32,694 euros (next to 40% less), the highest was in Ireland (135,200 euros), while the lowest in Bulgaria (12,040 euros).